Building bonds for sustainable growth: social capital and networking in Indonesian tourism development - Suri, Dia Meirina; Fikri, Rijalul; Amri, Pahmi; Sasmi, Dini Tiara (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
This research aims to identify and analyze the utilization of social capital in developing tourist attractions and networking in Kampar Regency. This study focuses on two potential tourist attractions owned by Kampar Regency, namely the Pulau Cinta tourist attraction and the Ulu Kasok views. The research design used is qualitative interpretative; in collecting information, primary data was obtained through observation and in-depth interviews. The interview results were entered into the Nvivo 12 Plus data processing application for coding and then analyzed using graphs and crosstab. The triangulation technique was used to obtain valid and credible results. The research findings show that the identified social capital in developing tourist attractions in Ulu Kasok and Pulau Cinta are networks built online and offline. First, tourist attraction organized online and offline promotions to attract visitors, but the improvement of the online platform requires further enhancement. Second, communication with stakeholders and the local community necessary to improve. Third, trust building between tourism destinations organizer and the local community enables tourist attractions to develop, and the fourth is Information openness about tourism destinations. The contribution of this research suggests maximum efforts in utilizing social capital in developing sustainable tourism destinations, through strengthening social networks, building trust, and enhancing communication among stakeholders and local communities.